ANALISIS AKUNTABILITAS KINERJA BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN KOTA BANJARBARU - Ade Hermawan (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
The conclusion from the data obtained from the informants' answers and juxtaposedwith the accountability performance report data of the Banjarbaru City Personnel,Education and Training Agency is that the Performance Accountability of theBanjarbaru City Personnel, Education and Training Agency is Good.